Peak power output in the power clean -the influence of relative strength - Beard, A.; Burnett, A.; Newton, R. U. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
The aim of this study was to determine whether athletes of higher relative strength maximise their power output at higher percentages of their 1RM in the power clean. Twenty-nine male athletes (power clean 1 RM = 99.2 ± 18.9 kg) performed two power cleans at 10% increments from 50% to 100% of 1 RM. Bar displacement was collected by a Ballistic Measurement System (BMS) and power output was calculated using system mass (SM) and bar mass (BM) methods. Optimal loads were 50% and 90% for the SM and BM methods respectively. However, a limitation of the study was that loads below 50% of 1RM were not examined. Relative strength was not related to percentage of 1 RM at which maximal power output was achieved.